Ecological-geomorphological transformations of inert landscape components in industrial zones - Zelenchuk, I. D. (Man and Environment. Issues of Neoecology, 2025)
Purpose. Comprehensive assessment of eco-geomorphological changes in inert components of the landscape caused by intensive construction activity in newly developed industrial zones of Ukraine, with consideration of the use of modern prefabricated building technologies. Methods. The field investigations, systemic and comparative geographical analysis, statistical, morphometric assessment, as well as the method of correlation and comparison Results. The results of field and analytical investigations demonstrated that construction activity constitutes a determining factor in the formation of zones with intensive technogenic pressure on soil cover. The highest levels of heavy metal contamination were recorded within active construction sites and adjacent material storage areas. Specifically, zinc (Zn) concentrations in these locations corresponding to the category of extremely high contamination according to the classification criteria for ecological soil quality assessment. Regression analysis revealed a statistically significant inverse correlation between the distance from the construction activity center and the accumulation level of heavy metals in the soil profile. Within the facies subjected to prolonged engineering intervention, a marked transformation of the vegetation structure was observed. Areas exposed to mechanical soil disturbance are characterized by a reduction in natural vegetation cover, a decline in species diversity, and the dominance of adaptive, primarily invasive, species. The displacement of biocenotic equilibrium promotes the exclusion of autochthonous flora species characteristic of the (natural) sites under investigation, leading to the formation of monodominant communities with low ecological resistance and impaired capacity for natural regeneration. Conclusions. The development of industrial zones in areas predominantly used for agriculture and forestry leads to significant ecogeomorphological transformations of the inert components of the landscape. The application of an integrated methodological approach enabled the quantitative assessment of changes in morphostructure, soil cover, and hydrological regime, as well as the detection of increased heavy metal contamination in soils within construction sites. Disruptions in the interaction between inert and biotic components of geosystems were identified, resulting in reduced ecological resilience. The findings can serve as a scientific basis for optimizing spatial planning, implementing monitoring measures, and guiding environmental management of industrial infrastructure development in agro-landscapes.